Effect of tooth brushing on color changes of esthetic restorative materials - Alzayer, Fatima; Alawami, Roaa (International Journal of Research in Medical Sciences, 2018)
Background: The major problem of dental restorative material over time is color changes, and this discoloration is caused by either intrinsic or extrinsic factors. Intrinsic factors include the staining of the material itself caused by changes in the resin matrix and the interface between matrix and fillers. Methods: The study was conducted using resin composite material (shade A2), and four solutions (distilled water, strawberry, pomegranate, and red grape juices). The specimens were distributed into four groups for immersion in one of the four solutions. Authors divided each group into brushing and non-brushing subgroups. Results: When immersed in water, shade was changed from A2 to A3.5 and A4 (light to dark) in brushing group and no overall change was noticed in non-brushing group. However, there was statistically significant difference between the two groups. Conclusions: All types of juices caused distinct color change. However, brushing caused more color change as compared to specimens with no brushing.